PEMBUATAN GAMELAN MOULDING JENIS BONANG BARUNG DI PT. YPTI KALASAN YOGYAKARTA - Rahman, Nur Setyo; Jatilinuar, Setya Rahdiyatmi Kurnia; Marsudi, Marsudi (IDEA: Jurnal Ilmiah Seni Pertunjukan, 2023)
Penelitian ini berjudul “Pembuatan Gamelan Moulding Jenis Bonang Barung. Gamelan moulding adalah gamelan yang menggunakan teknik moulding (cor) dalam pembuatannya sehingga memiliki rangkaian khusus pada proses pembuatan maupun pelarasan yang berbeda dengan gamelan pada umumnya. Berdasarkan latar belakang tersebut penelitian ini bertujuan untuk mengetahui proses pembuatan dan pelarasan bonang barung moulding di PT. YPTI Kalasan Yogyakarta. Metode penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan deskriptif analisis. Data penelitian didapatkan dari observasi dan praktik langsung di lapangan maupun wawancara dengan narasumber. Data yang didapatkan kemudian dianalisis dan dideskripsikan secara rinci. Hasil penelitian ini antara lain 1) bonang barung moulding di PT. YPTI menunjukkan produktivitas dan efisiensi dalam pembuatan gamelan, baik dari aspek bahan maupun waktu; 2) bahan yang digunakan untuk membuat bonang barung moulding berupa perunggu dan kuningan dengan ketebalan 3ml; 3) pembuatan gamelan moulding jenis bonang barung di PT. YPTI menggunakan teknik cor atau gravity casting yang didukung penggunaan alat modern; 4) metode dalam pelarasan bonang barung hanya diatur ketebalannya menggunakan gerinda untuk meninggikan maupun merendahkan disesuaikan frekuensi nada yang sudah ditentukan. Untuk mengetahui nadanya frekuensi sebagai tolak ukur melalui proses perekaman terlebih dahulu.MAKING OF BONANG BARUNG GAMELAN MOULDING AT PT. YPTI KALASAN YOGYAKARTAThis research is entitled "Making Gamelan Molding Bonang Barung Type. Gamelan molding is a gamelan that uses molding techniques (casting) in its manufacture so that it has a special sequence in the manufacturing process and tuning that is different from gamelan in general. Based on this background, this study aims to determine the process of making and adjusting bonang barung molding at PT. YPTI Kalasan Yogyakarta. The research method used is qualitative research with a descriptive analysis approach. Research data were obtained from direct observation and practice in the field as well as interviews with informants. The data obtained is then analyzed and described in detail. The results of this study include 1) bonang barung molding at PT. YPTI shows productivity and efficiency in making gamelan, both from the material and time aspects; 2) the materials used to make bonang barung molding are bronze and brass with a thickness of 3 ml; 3) making gamelan molding of the bonang barung type at PT. YPTI uses cast or gravity casting techniques supported by the use of modern tools; 4) the method of tuning the bonang barung is only to adjust the thickness using a grinder to raise or lower it according to a predetermined tone frequency. To find out the tone frequency as a benchmark through the recording process first. YPTI uses cast or gravity casting techniques supported by the use of modern tools; 4) the method of tuning the bonang barung is only to adjust the thickness using a grinder to raise or lower it according to a predetermined tone frequency. To find out the tone frequency as a benchmark through the recording process first. YPTI uses cast or gravity casting techniques supported by the use of modern tools; 4) the method of tuning the bonang barung is only to adjust the thickness using a grinder to raise or lower it according to a predetermined tone frequency. To find out the tone frequency as a benchmark through the recording process first. This research is expected to be able to provide benefits to the wider community regarding how to process waste into goods that have a myriad of benefits.